Cultivating Leadership Character for Elementary Students - Nicken Destriana; Arwina Karmudiandri; Nurwanti Nurwanti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This community service activity aims to build the character and potential of early childhood to have a spirit of leadership in the future. This program was initiated as a response to the need to equip children with the basics of leadership, moral integrity, and socio-emotional skills to face real-world challenges. The methods used include a participatory approach with a series of interactive activities designed to introduce basic leadership concepts such as responsibility, courage, and simple decision-making. The results of this activity have shown a notable positive influence on the character development of young children and serves as a foundation for cultivating leadership skills within the school setting. It is anticipated that the program will yield sustained benefits for the character growth of students at SD Petra Alpha School Kembangan, West Jakarta.